Determination of energetic positions of electronic states and the exciton dynamics in a π-expanded N-heterotriangulene derivative adsorbed on Au(111) - Steidel, Jakob; Michalsky, Ina; Ajdari, Mohsen; Kivala, Milan; Tegeder, Petra (Physical chemistry, chemical physics, 2024)
Bridged triarylamines, so-called N-heterotriangulenes (N-HTAs) are promising organic semiconductors for applications in optoelectronic devices. Thereby the electronic structure at organic/metal interfaces and within thin films as well as the electronically excited states dynamics after optical excitation is essential for the performance of organic-molecule-based devices. Here, we investigated the energy level alignment and the excited state dynamics of a N-HTA derivative adsorbed on Au(111) by means of energy- and time-resolved two-photon photoemission spectroscopy. We quantitatively determined the energetic positions of several occupied and unoccupied molecular (transport levels) and excitonic states (optical gap) in detail. A transport gap of 3.20 eV and an optical gap of 2.58 eV is determined, resulting in an exciton binding energy of 0.62 eV. With the first time-resolved investigation on a N-HTA compound we gained insights into the exciton dynamics and resolved processes on the femtosecond to picosecond timescale.
Online veröffentlicht: 24. Mai 2024
Gesehen am 28.11.2024